The global mobility “international employer” audit: charting the territory - Dickmann, Michael; Barzantny, Cordula; Enser, David (University of Bamberg Press, 2022)
Many authors and global mobility (GM) leaders ask for good data to base their expatriation decisions on. After all, where business insights lack it is rare that organizational decisions are high quality, agile and responsive to changing circumstances. One of the key aims of GLOMO was to develop a tool that helps important GM stakeholders, and in particular senior GM leaders, to monitor, analyse and refine their global mobility approaches. This chapter outlines pertinent GM design considerations in relation to strategic and operational pre-expatriation, on-assignment, and post-assignment decisions. In addition, it gives sample items of important performance indicators so that the reader gains an insight into core GM objectives. It shows how the GLOMO European research project is useful for organizations to improve their approaches to planning and managing the global mobility of employees.
Keywords: Expatriation; Global mobility